Getting Back to the State: Policing the Covid-19 Pandemic - Dammert-Guardia, L (Routledge, 2023)
This paper analyzes the impact of the pandemic (from 2020 to 2021) on levels of trust and legitimacy of the Chilean police (Carabineros) by the population in the metropolitan area of Santiago, Chile. Based on a pseudo-panel method and a cohort fixed-effects regression model that controlled for unobserved time invariant heterogeneity, we found a significant increase in police legitimacy during the pandemic (on average, 63%, among the adult residents of the region, based on the police legitimacy index comprising six perceptual variables). Evidence suggests that the perceived performance of the Carabineros during the pandemic served to recover the trust of citizens, at least temporarily, even when this intervention entailed the enforcement of anti-popular measures. © 2023 Informa UK Limited, trading as Taylor & Francis Group.